PRAKTIK MANAJEMEN PAKAN DAN RISIKONYA TERHADAP PENYEBARAN AFRICAN SWINE FEVER DI KOTA KUPANG - Toha, Larry Richard Wellem; Sanam, Maxs U. E.; Gelolodo, Maria Aega (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2021)
In early 2020 a high mortality of pigs in Malacca Regency, East Nusa Tenggara Province was confirmed as an ASF infection which then spread to all of Timor Island, Flores Island, and Sumba Island. One of the risk factors for the spread of ASF is swill feeding. The purpose of this study was to study the feed management practices of pig farmers during the ASF outbreak and to measure the relationship between feed management practices and the ASF outbreak in Kupang City. The study used a case-control study approach to study feed management practices for pig farmers during the outbreak and their relationship to ASF. A total of 69 farmers who had experienced the incidence of dead and sick pigs were taken as case samples and 21 farmers were randomly selected from around the area as controls. The data in this study were analyzed by descriptive statistics and bivariate analysis was used to measure the relationship between feed management practices and the incidence of ASF. The results of the bivariate analysis showed that swill feeding practice had a significant correlation with the incidence of ASF (P 0.038<0.05) with OR (2.94), while the factor of cooking or not cooking feed before being given to pigs was also significantly correlated with the incidence of ASF (P 0.003<0.05) with OR (0.1). In conclusion, based on epidemiological analysis, the factor of swill feeding practice that is not cooked is highly correlated with the incidence of ASF in Kupang City.